PELATIHAN RANDAI BAGI BERKEBUTUHAN KHUSUS (DISABILITAS) DI PANTI SOSIAL BINA NETRA KURANJI KOTA PADANG - Reyhan Imansyah; Esy Maestro; Yuliasma Yuliasma (FBS Universitas Negeri Padang, 2015)
Abstract This research was designed for revealing and describing Randai training for the students with visual impairment at Panti Sosial Bina Netra Kuranji Kota Padang related to movement, music, and plot. This was a qualitative research which used descriptive method. The data was gotten through direct observation and interview. The data was analyzed based on Randai training process joined by the students with visual impairment. The result of this research was expected to increase the students' independence and self-confidence although they were visually impaired. They were initially unwilling to perform Randai as they were afraid of being mocked by others. But, the motivation given by the trainers and the teachers teaching at panti had made them enthusiastic to perform Randai. The Randai skill they got made them feel better even though they could not present it as normal people did. Regardless their visual impairment, in the process of training, the students were very passionate. Key words: Randai Training For The Students With Visual Impairment